Kontribusi Pajak Rumah Makan terhadap Peningkatan Pendapatan Asli Daerah Kota Parepare (Analisis Ekonomi Islam) - Soumena, Moh. Yasin; Rukiah; Wulandari, Kurnia Tri Wulandari; Putra, Muamar Adi; Adiyaswari, Achwani; Amalia Anindita Jufri (Al Rikaz: Jurnal Ekonomi Syariah, 2022)
The objective of this study is to examine how the implementation of the restaurant tax collection system, the barriers encountered in its execution, and the subsequent utilization of the collected funds have contributed to the increase in local revenue in the city of Parepare. This research employs a qualitative methodology with a descriptive approach, utilizing both primary and secondary data sources. Data collection methods encompass observation, interviews, and documentation. The analysis involves data reduction, presentation, and drawing conclusions. The findings of this study indicate the following: 1) The execution of the restaurant tax collection system by the Regional Finance Agency of Parepare City adheres to the government regulations stipulated in the Republic of Indonesia number 55 of 2016 and PERWALI number 39 of 2020. These regulations are aligned with the principle of maslahah. 2) Challenges in restaurant tax collection primarily arise from taxpayer dishonesty in calculating, depositing, and reporting taxes. Additionally, instances of negligence among tax collectors are observed, contradicting the essential principles of honesty and trustworthiness within Islamic economics. 3) The revenue generated through restaurant tax collection is directed towards community support and regional development, conforming to Islamic economic principles, particularly the concept of maslahah. This contribution constitutes 2.75% of the total. In summary, this study underscores the significance of the restaurant tax collection system's adherence to legal regulations and ethical standards. Despite challenges, the resulting revenue contributes to community welfare and regional growth, in alignment with the principles of Islamic economics.